2001
DOI: 10.1097/00126334-200112010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Reproductive Life of Women Informed of Their HIV Seropositivity: A Prospective Cohort Study in Burkina Faso

Abstract: Our study shows a poor rate of HIV test sharing and a poor use of contraceptive methods despite regular advice and counseling. Pregnancy incidence remained comparable with the pregnancy rate in the general population. To improve this situation, approaches for involving husbands or partners in VCT and prevention of MTCT interventions should be developed, evaluated, and implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
3
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 20 publications
8
71
3
2
Order By: Relevance
“…32 Finally, it is difficult for a pregnant woman who knows she has HIV to have protected intercourse with her spouse if he is unaware of her serostatus. Condom use with regular partners is very low after antenatal HIV testing, 33 , and only increases when the partner has been notified of his wife's HIVpositive status 27 or has been tested himself. 34 A recent study in Abidjan has shown that, for all these reasons, HIV-positive women tended to inform their partner of their HIV status before opting for formula feeding for the baby, and when sexual activity was resumed.…”
Section: -25mentioning
confidence: 99%
See 1 more Smart Citation
“…32 Finally, it is difficult for a pregnant woman who knows she has HIV to have protected intercourse with her spouse if he is unaware of her serostatus. Condom use with regular partners is very low after antenatal HIV testing, 33 , and only increases when the partner has been notified of his wife's HIVpositive status 27 or has been tested himself. 34 A recent study in Abidjan has shown that, for all these reasons, HIV-positive women tended to inform their partner of their HIV status before opting for formula feeding for the baby, and when sexual activity was resumed.…”
Section: -25mentioning
confidence: 99%
“…39,40 In settings without couple VCT, the break-up of the relationship among HIV-positive women has also been documented, but was not related to notification of the partner. 33,42 It is possible that these break-ups do not result from a negative reaction of the partner, but rather occur because the woman prefers to separate rather than face the difficulties of a conjugal relationship coping with HIV infection.…”
Section: Couple-centred Approaches To Hiv Counselling and Testingmentioning
confidence: 99%
“…Malgré le risque de transmission maternofoetale qui demeure élevé dans les pays d'Afrique sub-saharienne, et en dépit des conseils de prévention qui sont délivrées aux femmes séropositives, leur fécondité reste élevée après le diagnostic [42][43][44]. Ainsi, en Côte d'Ivoire, le désir d'enfant demeure important après le dépistage chez la majorité des femmes, à l'exception de celles qui estiment avoir eu suffisamment d'enfants [13].…”
Section: Le Désir D'enfant : Entre Statut Social Et Gestion Du Risqueunclassified
“…Cultural factors were especially important in the desire to have children for PLHIV from sub-Saharan African countries (Nattabi et al, 2009). Craft et al(2007) reported that HIVpositive women who experienced high levels of personalized stigma were less likely to disclose their status to their partners and also more likely to desire having children (Oladapo et al, 2005;Phaweni et al, 2010) The sexual and reproductive desires of PLHIV are not perceived as significantly different from those who are not infected (Nebie et al, 2001). Additionally, the same human rights apply to those infected and not infected (Currie and de Waal, 2005).…”
Section: Introductionmentioning
confidence: 99%